Shear and bending performance of new type enhanced lattice truss structures. (December 2017) - Feng, Li-Jia; Xiong, Jian; Yang, Li-Hong; Yu, Guo-Cai; Yang, Wen; Wu, Lin-Zhi
Highlights: Shear and bending response of a new type hourglass truss structures were investigated. Shear strength of the hourglass truss were 40%–60% higher than the pyramidal truss. Bending strength of the hourglass beam was superior to that of the pyramidal beam. Abstract: In this work, the new type enhanced lattice (defined as hourglass) truss structures with the improved resistance of their core members and attached face sheets have been fabricated by an innovative interlocking method. The shear and bending properties of the produced sandwich structures characterized by three different relative densities have been investigated using various analytical methods and the obtained results were in good agreement with the experimental data. The truss failure under shear loading was dominated by the inelastic buckling of the truss members, while the four possible analytical models describing the bending properties and failure mechanism of the hourglass truss beams included elastic face sheet buckling, face sheet yielding, elastic core member buckling, and core member yielding were studied. The bending specimens, which were designed by constructing failure mechanism maps, were used to examine the yielding behavior of the truss core members as well as the elastic buckling and yielding of the face sheet members. The obtained results revealed that the specific shear strengths and bending failure loads of the studied hourglass truss structures were superior to those of pyramidal truss structures, and that the former could be considered promising candidates for manufacturing lightweight structures with high specific strength. Graphical abstract: